Multi-sensor monitoring for optimising printing parameters of laser powder bed fusion (L-PBF) processes - Allen Hum Jun Wee; Qing Yang Lu; Truong Do; Ngoc Vu Nguyen; Tuan Tran (Virtual and Physical Prototyping)
Laser powder bed fusion (L-PBF) is widely recognised as a reliable technology for metal additive manufacturing (AM). However, industrial adoption of this technology still requires established methods to ensure its products' quality and optimise its printing parameters, either using in-process monitoring data or post-process characterisation. In this study, we utilise both visible-light and thermal imaging sensors to monitor L-PBF processes and provide a quantitative characterisation of the printed layers. For each layer of a printed part, we use a combination of thermal information and surface appearance to develop quality indicators capable of distinguishing printed parts with acceptable quality and those prone to overheating and lack of fusion. We also demonstrate the use of these quality indicators in detecting thermal deformation for overhanging structures.